Bioleaching in brackish waters—effect of chloride ions on the acidophile population and proteomes of model species - Zammit, Carla; Mangold, S.; rao Jonna, V.; Mutch, Lesley; Watling, Helen; Dopson, M.; Watkin, Elizabeth (Springer-Verlag, 2012)
High concentrations of chloride ions inhibit the growth of acidophilic microorganisms used in biomining, a problem particularly relevant to Western Australian and Chilean biomining operations. Despite this, little is known about the mechanisms acidophiles adopt in order to tolerate high chloride ion concentrations. This study aimed to investigate the impact of increasing concentrations of chloride ions on the population dynamics of a mixed culture during pyrite bioleaching and apply proteomics to elucidate how two species from this mixed culture alter their proteomes under chloride stress. A mixture consisting of well-known biomining microorganisms and an enrichment culture obtained from an acidic saline drain were tested for their ability to bioleach pyrite in the presence of 0, 3.5, 7, and 20 gL−1 NaCl. Microorganisms from the enrichment culture were found to out-compete the known biomining microorganisms, independent of the chloride ion concentration. The proteomes of the Gram-positive acidophile Acidimicrobium ferrooxidans and the Gram-negative acidophile Acidithiobacillus caldus grown in the presence or absence of chloride ions were investigated. Analysis of differential expression showed that acidophilic microorganisms adopted several changes in their proteomes in the presence of chloride ions, suggesting the following strategies to combat the NaCl stress: adaptation of the cell membrane, the accumulation of amino acids possibly as a form of osmoprotectant, and the expression of a YceI family protein involved in acid and osmotic-related stress.